PERBANDINGAN TINGKAT INFLASI PROVINSI RIAU DENGAN TINGKAT INFLASI PROVINSI YANG BERBATASAN LANGSUNG DENGAN PROVINSU RIAU (SUMATERA UTARA, SUMATERA BARAT DAN JAMBI) SELAMA PERIODE 2009 - 2013 - Harry Permana Putra; Yusbar Yusuf; Syafril Basri (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2014)
Inflation is a process of rising prices in general and continuous with regard to market mechanisms induced by different factor,among other things, incrased community consumption, excess liquidity in the market that fueled the consumption or even speculation and the distribution of goods that are not fluently. In other words, inflation is also the currency values serially.Inflation is a process, not an event of high or low price levels. This means that the price level is considered high is not necessarily indicate inflation. The data used in this research is the use of secondary data which come from Bank of Indonesia, BPS, and Finance of Indonesia. The data are obtained the quarterly reports and the annual report. The research results are either quarterly or annually, inflation increases occurred at a quarterly-III every year due to the quarter to concide with Ramadhan and Eidul-Fitri.The inflation hike was mostly experienced by volatile food group. Rising inflation also accompanied the influx of new education school year due to soaring prices for all school levels. And inflation rise on quarter-III this also happens annually in every province, Riau, West Sumatera,North Sumatera dan Jambi.Keywords: Inflation